2020
DOI: 10.1080/15622975.2020.1813329
|View full text |Cite
|
Sign up to set email alerts
|

Impaired response inhibition during a stop-signal task in children with Tourette syndrome is related to ADHD symptoms: A functional magnetic resonance imaging study

Abstract: Objectives: Tourette syndrome (TS) is characterised by the presence of sudden, rapid movements and vocalizations (tics). The nature of tics suggests impairments in inhibitory control. However, findings of impaired inhibitory control have so far been inconsistent, possibly due to small sample sizes, wide age ranges, or not taking medication use or attention-deficit/hyperactivity disorder (ADHD) comorbidity into account. Methods: We investigated group differences in response inhibition using an fMRI-based stopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 77 publications
5
7
0
Order By: Relevance
“…These results suggest that comorbid ADHD was associated with greater disability than TD alone. Our findings are consistent with previous studies indicating that co-existing ADHD often causes more psychosocial impairment for children and adolescents with TD than the severity of the tics themselves [ 8 , 13 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results suggest that comorbid ADHD was associated with greater disability than TD alone. Our findings are consistent with previous studies indicating that co-existing ADHD often causes more psychosocial impairment for children and adolescents with TD than the severity of the tics themselves [ 8 , 13 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…These two studies showed that CBIT may promote neurocognitive changes and normalization of deficits in cortico-striato-thalamo-cortical circuits in individuals with TD, which may account for our findings of an improvement in inattention, psychosomatic, anxiety and impulsivity-hyperactivity symptoms. As ADHD and TD share both common and different brain regions [ 11 , 13 , 36 ], it is conceivable that the improvements on the CRPS-R scores may be related to the positive effects of the core therapeutic techniques of CBIT; namely, tic awareness training, stress management and tic suppression by implementing habit reversal skills. These techniques may have a positive effect on certain neurological circuits associated with the impaired inhibitory performance and with attentional and sensory regulation mechanisms underlying both ADHD and TD [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the association between TS and disinhibition, other studies have pointed to the opposite pattern, namely, an increased IC in TS. We previously found children with TS to be equal or superior regarding response inhibition to typically developing controls when inhibiting fast, impulsive actions [13], with another study demonstrating the increased activation of prefrontal areas in children with TS during tasks that require IC [14]. Together, these results support the hypothesis that children with TS develop neuroplastic compensatory mechanisms due to the ongoing suppression of tics [15,16].…”
Section: Introductionsupporting
confidence: 62%